livros infantis adequados para uma criança com deficiência visual: a experiência de bolsistas PIBID da FFC/UNESP/Marília - Oliveira, Fátima Inês Wolf de [UNESP]; Rodrigues, Ariane da Silva [UNESP]; Scavoni, Mariana Paula Pereira [UNESP]; Ferrari, Marina Serracchiani [UNESP] (My University, 2012)
This article tells the experience of some scholarship holders of Subproject PIBID Pedagogy Literacy FFC, who have developed, between its activities: planning, analysis, confection and adequacy of books of infantile histories so that they can be read and better understood for a child with visual deficiency. The idea arose from the fact that the school in which the pupil is enrolled does not have in its collection such resources. The books followed the criteria of adequacy and present in the literature of specific preparation area and the results pointed to the schoolgirl showed interest and motivation to run the task to read the stories with the adjustments that are made.

Este artigo narra a experiência de algumas bolsistas do Subprojeto PIBID Pedagogia Alfabetização FFC, que têm desenvolvido, entre suas atividades: planejamento, análise, confecção e adequação de livros de histórias infantis para que possam ser lidos e melhor compreendidos por uma criança com deficiência visual. A ideia surgiu a partir da constatação que a escola em que a aluna está matriculada não possui em seu acervo tais recursos. Os livros seguiram critérios de adequação e confecção presentes na literatura específica da área e os resultados apontaram que a aluna demonstrou interesse e motivação para a execução da tarefa de ler as histórias com as adequações realizadas.
Adapted infantile books for a child with visual deficiency: the experience of scholarship holders pibid of the FFC/UNESP/Marília
Keywords: Inclusão Escolar; Livros Infantis Adaptados; Ensino de alunos com deficiência visual